Protasi S. Loving people for who they are (even when they don’t love you back) / trans. from Engl. R. L. Kochnev - R. L. Kochnev (Омский научный вестник: Серия "Общество. История. Современность")
The debate on love’s reasons ignores unrequited love, which–I argue–can be as genuine and as valuable as reciprocated love. I start by showing that the relationship view of love cannot account for either the reasons or the value of unrequited love. I then present the simple property view, an alternative to the relationship view that is beset with its own problems. In order to solve these problems, I present a more sophisticated version of the property view that integrates ideas from different property theorists in the love literature. However, even this more sophisticated property view falls short in accounting for unrequited love’s reasons. In response, I develop a new version of the property view that I call the experiential view. On this view, we love a person not only in virtue of properties shaped by and experienced in a reciprocal loving relationship, but also in virtue of perspectival properties, whose value can be properly assessed also outside of a reciprocal loving relationship. The experiential view is the only view that can account not only for reciprocated love’s reasons, but also for unrequited love’s reasons